Cultural context of work and management practices in selected De Luxe hotels in Metro Manila - Ramos, Mary Anne R. (2000)
This descriptive research was designed to study the cultural context of work and management practices "in situ" in the local hotel organization. There were three types of respondents: Filipino rank and file employees, Filipino managers and expatriate managers. An in-depth interview was administered to elicit information about their preferred work values, motivation strategies, and conflict resolution styles. The responses were used as the content in formulating the survey questionnaires which were refined and pre-tested. Data were analyzed through descriptive statistics like frequency distribution and several statistical analyses using Statistical Package for Social Science (SPSS). The result of the factor analysis revealed that work values considered important for Filipino rank and file employees were generally "relational" in nature, while preferred work values of Filipino managers focus on "work opportunity", or those that enhance their effectiveness as managers. Expatriate managers' preferred work values reflected their "seriousness" in the workplace. This conformed to their being professional and output-oriented. Among the Filipino rank and file employees studied, correlation data showed that "Management Style" (r=.72) had the nearest correlation to their overall satisfaction of the expatriates' management practices in the work setting, whereas, "Participative Leadership Style" (r=.72) and "Work Opportunity" (.71) highly correlated with the Filipino managers' overall satisfaction. Correlation analysis also showed association between satisfaction of expatriate managers to Filipino employees' "Responsibility" (r=-.61) and "Job Freedom" (r=.52). Mean ratings and highest ranked work values as indicated by expatriate managers for Filipino rank and file employees were on "Work Standards" and "Management Style". On the other hand, the Filipino managers' perspective on salient work values of expatriate managers were in the categories of "Work Opportunity" and "Participative Leadership Style". The responses of the expatriate managers on ranked work values elucidated that "Professionalism" was viewed as vital to achieving high level of productivity. For the three types of respondents, a gap analysis was made to determine the difference between indicated important work values and actual performance. Data revealed that gaps between expected work values and actual practice of expatriate managers according to the Filipino rank and file employees were modest. Gaps were predominant in work values like: "approachable" (.82), "listen to the point of view of others" (.77), "They make me feel that I am a member of the family" (.72), "motivate employees" (.66) and "provide employees a chance to develop" (.64). On the contrary, gap scores on preferred work values and behavior of expatriate managers according to Filipino managers were relatively high. Disparities were found in the following work traits: "leader by example" (1.0) posted the highest gap, followed by "professional" (.93), "provide an environment that supports cooperation" (.83), "provide employees opportunity to develop" (.81) and "do not have favoritism" (.81). Finally, the wider gap scores of expressed important work values of Filipino employees versus actual management practice by the expatriate managers underlined discrepancies in the following: "always o time" (2.3), "sincere" (1.76), "have their own goal and work for that goal" (1.46), "responsible and dedicated" (1.4) and "productive" (1.37). These results clarified which work and management practices could be producing a short fall in expectations in the workplace. Furthermore, findings also identified which work values needed to be developed to improve work relations and create a more positive job environment for Filipino employees and expatriate managers that could contribute towards achieving the organizational goals. In terms of preferred conflict resolution style, "compromise" appeared to be the most favored style by the Filipino rank and file employees, Filipino managers and expatriate managers. This meant coming up with a consensus for the benefit of the two conflicting parties. Finally, motivation strategies of expatriate managers used for Filipino subordinates were "task-oriented", reflecting their desire to motivate Filipino employees to work with challenging tasks and to pursue and work for their desired goal. Filipino managers' motivation strategies for expatriate managers who were either their superiors or equals, emulated their value for "accommodation" as a manner of preserving harmonious social relationships with them. Recognizing different work values and how these positively affect the organizational behavior elicit positive outcomes like efficiency and productivity, thus, pervading a more effective inter-cultural organization.